Literasi Digital dengan Perilaku Konsumtif pada Generasi Z - Kurniawati, Linda; Pratitis, Niken Titi; Arifiana, Isrida Yul (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
This study aims to determine the relationship between digital literacy and online shopping consumer behavior in generation Z. This study uses a quantitative research type using a correlational method. The sampling technique in this study used the Quota Sampling technique with a sample size of 115 generation Z aged 20-27 years. This study uses data instruments, namely the Digital Literacy Scale and the Consumptive Behavior Scale. Data were analyzed using the help of the Pearson correlation test with SPSS software version 25 for Windows. The results of the product moment analysis showed a relationship between digital literacy and consumptive behavior obtained a correlation value = -138 with a significance of P = 0.141> 0.05 meaning that there is no relationship between digital literacy and consumptive behavior, so the hypothesis is rejected.